Effect of nutrition assessment, counselling and support integration on mother-infant nutritional status, practices and health in Tororo and Butaleja districts, Uganda: A comparative non-equivalent quasi-experimental study - Samalie Namukose; Gakenia Wamuyu Maina; Suzanne N Kiwanuka; Fredrick Edward Makumbi (BMC, 2024)
Abstract Background Malnutrition remains a health challenge for women aged 15 to 49 years and their infants. While Nutrition Assessment Counselling and Support (NACS) is considered a promising strategy, evidence of its effectiveness remains scanty. This study assessed the effect of the comprehensive NACS package on the mother-infant practices, health and nutrition outcomes in two districts in Eastern Uganda. Methods A comparative non-equivalent quasi-experimental design was employed with two groups; Comprehensive NACS (Tororo) and Routine NACS (Butaleja). Pregnant mothers were enrolled spanning various trimesters and followed through the antenatal periods and post-delivery to monitor their health and nutrition status. Infants were followed for feeding practices, health and nutritional status at birth and weeks 6, 10, 14 and at months 6, 9 and 12 post-delivery. Propensity score matching ensured study group comparability. The NACS effect was estimated by nearest neighbour matching and the logistic regression methods. Statistical analysis utilised STATA version 15 and R version 4.1.1. Results A total of 666/784 (85%) with complete data were analysed (routine: 412, comprehensive: 254). Both groups were comparable by mothers' age, Mid Upper Arm Circumference, prior antenatal visits, meal frequency, micronutrient supplementation and instances of maternal headache, depression and diarrhoea. However, differences existed in gestation age, income, family size, education and other living conditions. Comprehensive NACS infants exhibited higher infant birth weights, weight-for-age z-scores at the 3rd -6th visits (p < 0.001), length-for-age z scores at the 4th -7th visits (p < 0.001) and weight-for-length z-scores at the 3rd − 5th (p < = 0.001) visits. Despite fewer episodes of diarrhoea and fever, upper respiration infections were higher. Conclusions The comprehensive NACS demonstrated improved mother-infant nutritional and other health outcomes suggesting the need for integrated and holistic care for better maternal, infant and child health.